How to Strengthen the Management of Government Guarantees. (IMF How To Notes; How-To Note, 2017)
This note highlights commonly observed weaknesses in the management of government guarantees, good practices, and measures governments could take to strengthen: (i) the evaluation of guarantee proposals; (ii) the quantification of risks arising from guarantees and their mitigation; and (iii) the budgeting, accounting, monitoring, and disclosure of guarantees.